ANALYSIS OF THE APPLICATION OF GREEN MARKETING TO ENHANCE CONSCIOUS CONSUMPTION (A CASE STUDY OF LED LAMPS’ CONSUMER IN MANADO) - Malia, Mario A. N. (Universitas Sam Ratulangi, 2018)
Abstract: The environment is getting worse day by day that make people need to take care the environment to keep living healthy this planet. Because everything comes under an environment, people in these days start concerning about the environmental problem that is continuously increased. People start to think the way how to protect the natural environment. This research aims to identify consumer’s conscious consumption toward green product. This is a qualitative research. Fifteen consumers of LED lamp had been interviewed for collecting the data. The results indicated that most of the people looking for the function of the product when they want to buy something, in this case LED lamp. When people want to buy a product, people considered on the benefits of the product. The way of company to do their advertising is really important, because if the information of the product delivered in the right way, it will raise the number of consumers. This research also found that the level of awareness among people who lives in Manado is high, but not all of those people’s awareness they take into an action, even though people already have the desire to participate in the green movement. High level of environmental awareness in Manado must be implemented into their daily life by people. Keywords: green marketing, green product, green price, green promotion, environmental awareness, conscious consumption, LED lamps.